Portable wide-field digital imaging for screening of neonatal visual impairment causes in Rio de Janeiro, Brazil: a budget impact analysis. Issue 6 (10th June 2022) - Haefeli, Lorena M; Neves, Luiza M; Zin, Andrea; Costa, Ana Carolina Carioca; Farias Meira de Vasconcelos, Zilton; Pinto, Marcia
Abstract : Objective: To estimate the budget impact of portable wide-field digital imaging incorporation on screening neonatal causes of childhood blindness and visual impairment in Rio de Janeiro, Brazil. Design: Budget impact analysis. Setting: Rio de Janeiro, Brazil. Primary and secondary outcome measures: The primary outcome was the direct cost of indirect binocular ophthalmoscopy, red reflex test and portable wide-field digital image screening comprising all babies born in Rio de Janeiro's government maternity wards. The secondary outcome was the budget impact of implementing portable wide-field digital image screening in Rio de Janeiro, Brazil. Results: Considering 100% coverage of maternity wards, the total budget impact between 2020 and 2024 would be US3 820 706.04, ranging from US3 139 844.34 to US6 099 510.35. The additional cost would be US3 124 457.28, ranging from US2 714 492.26 to US4 880 608.63. Conclusion: The cost of universal digital imaging screening corresponds to less than 1% of the government health budget of the city of Rio de Janeiro. The information provided in this study may help government decision-makers evaluate the feasibility of implementing this new strategy in the municipal setting. Further health economic evaluations should be performed to verify the affordability of the implementation of this screening strategy in the Brazilian scenario, taking into account scarce human resources.